Вай кырӟалом, эшъёс!: кырӟанъёс / люказы: Л. В. Перевозчикова, А. Г. Иванова, С. А. Ильин - Перевозчикова Лидия Васильевна (Удмурт кырӟанъёс, 1993)
Экземпляры: кр (20220214) / Инвентарный номер: 27623 / Цена: / Авт.знак: В 12 / ГРНТИ: 13 / ББК: 85.314(2Рос=Удм)